Docetaxel-loaded anti-PSMA-functionalised PLGA-PEG nanoparticles suppress cell migration in LNCap prostate cancer cells and promote cell death in 3D spheroids - Essa, Divesha; Kaur, Mandeep; Kumar, Pradeep; Choonara, Yahya Essop (Frontiers in Nanotechnology, 2026)
IntroductionPolymeric nanoparticles have been used in drug delivery to treat cancer by selective targeting of tumour cells and inducing programmed cell death. Previously optimized nano-systems loaded with docetaxel and functionalized with anti-PSMA antibody were used to investigate targeting of prostate cancer cells using prostate-specific membrane antigen (PSMA) as a target for receptor-mediated endocytosis and enhanced cellular uptake.MethodsCell migration, apoptosis, cell cycle, and generation of reactive oxygen species were evaluated using in vitro assays on PSMA-positive LNCap and PSMA-negative PC-3 prostate cancer cells. Thereafter, the growth inhibition and viability of 3D spheroids cultured from LNCap cells were measured, and the efficacy of the targeted nano-system and its interaction with the spheroids were investigated using fluorescence microscopy.ResultsIn LNCap cells, the targeted system outperformed the non-targeted counterpart, resulting in migration inhibition of 89% ± 8.4% versus 48.1% ± 2.7% and G2/M phase arrest of 30.3% ± 3.0% versus 15.8% ± 2.8%. Conversely, treatment of PSMA-negative PC-3 cells resulted in no statistically significant changes to migration or cell cycle progression (p > 0.05), indicating that the therapeutic potency of the targeted system is mediated by PSMA-receptor-mediated endocytosis, a pathway unavailable in PC-3 cells. There was also higher inhibition of 3D LNCap spheroids by both nano-systems than by free docetaxel, with 67.8% ± 5.5% and 17.6% ± 4.6% inhibition for the targeted and non-targeted systems, respectively. Fluorescence microscopy showed that the targeted system was able to penetrate the 3D spheroid structure and cause cell death.DiscussionThe enhanced cellular activity and spheroid penetration of the targeted nano-system in LNCap cells, together with the lack of effect in PSMA-negative PC-3 cells, support PSMA-receptor-mediated endocytosis as the key uptake mechanism and suggest the potential of this anti-PSMA-functionalised PLGA-PEG nano-system as a targeted nanocarrier for docetaxel in prostate cancer.